Ecological protection for natural protected areas based on landsenses ecology: a case study of Dalinor National Nature Reserve. Issue 8 (16th November 2020) - Yu, E.; Cui, N.; Quan, Y.; Wang, C.; Jia, T.; Wu, D.; Wu, G.
ABSTRACT: The global environment has been worsening, and governments around the world have realized that the establishment of natural protected areas is one of the important ways to achieve sustainable development. Natural protected areas are spatial carriers for protecting biodiversity, natural resources and cultural heritages, and play a vital role in achieving regional ecological security. Combined with the evolution rules of the complex ecosystem, this article establishes the protection framework and optimizes the protection strategies of natural protected areas with landsenses ecology as the main theoretical basis. Taking Dalinor National Nature Reserve as an example, protection strategies are analyzed from three aspects, namely protection objectives, protection contents and protection measures. Based on the three-zone management model of natural protected areas, the Internet of Things (IoT) is used to help managers better understand various data indicators of the residents, resources and rare species in natural protected areas; mix-marching data platform is used to conduct data analysis and quantitative evaluation. By doing so, protection strategies can be carried out through a process of melioration.